PENGARUH EKSPLORASI KARIR (CAREER EXPLORATION) DAN DUKUNGAN SOSIAL ORANGTUA (PARENTAL SOCIAL SUPPORT) TERHADAP KECEMASAN KARIR (CAREER ANXIETY) SISWA SMA - Nadya Rahmadani; Dede Rahmat Hidayat; Happy Karlina (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
One of the inhibiting factors that teenagers face in achieving their career success is anxiety and fear. Meanwhile, the search for self-identity is a common source of anxiety. This study aims to measure the effects of career exploration and parental social support on career anxiety level of students of State Senior High School 75 Jakarta. The ex-post facto research design adopted in this study is Multiple Correlation. The population involved in this study consists of 252 class XII students of the State Senior High School 75 Jakarta. The sample in this study consists of 155 students. The result of the research shows that the career exploration had no significant effect on career anxiety, it was decided that H0 is acceptable with a conclusion that the career exploration variable had no significant effect on career anxiety, whereas the parental social support had a significant effect on career anxiety. In overall, the career exploration and parental social support variables have a significant correlation in their impact on the students’ career anxiety.